External pressure headache. Literature review - Timofejavaitė , R.; Ryliškienė , K. (Neurologijos seminarai, 2021)
External pressure headache is a primary headache disorder caused by physiological non-damaging stimuli; it has clear intermittent presentation, simple treatment and prevention recommendations, and therefore does not get much attention in medical literature. However, as the epidemiological situation changes, healthcare workers as long-term users of personal protective equipment have a higher risk to experience this type of headache. The article provides a review of the classification of external pressure headaches, diagnostic criteria, headache characteristics, pathogenesis mechanisms, and headaches caused by personal protective equipment during COVID-19 pandemic.